Quasiclassical Trajectory Study of the Stereodynamics for the Au + H2 (v=0, j=0) → AuH + H Reaction (Journal of Atomic and Molecular Sciences, 2016)
The stereodynamics of the reaction Au+H$_2$ have been performed by usingquasi-classical trajectory (QCT) method on a global potential energy surface created byZanchet et al. at the collision energy of 1.8, 2.2, 3.0 eV. The calculation on $P(θ_r),$ $P(φ_r),$ and $P(θ_r,φ_r)$ and four polarization-dependent differential cross sections (PDDCSs) inthe center-of-mass (CM) indicate the dependence of the product polarization on collisionenergies. The product rotational angular momentum vector $j'$ is symmetric andperpendicular to $k$ direction according to the $P(θ_r)$ distributions. The $P(φ_r)$ distributionsaround $φ_r=270^{°}$ indicate that the rotational angular momentum vectors not onlyaligned along the y-axis direction, but also oriented to the y-axis negative direction.For the lower collision energy of 1.8eV, the ${\rm PDDCS}_{00}$ is symmetric on the forward andbackward scattering, probably due to the long lifetime complex created in the insertionreaction, while for the increasing collision energies, the prominent forward scatteringis all on account of that the reaction is controlled by direct stripping.
Keywords: stereodynamics; Au+H$_2$; quasi-classical trajectory; vector correlation.